Studies on freshwater Entomostraca in Greenland III. - Røen, Ulrik Ib (Meddelelser om Grønland, 1968)
During an investigation of the freshwaters of Peary Land, North Greenland , which took place in the summers of 1964 and 1966, a total of 34 freshwater localities was studied ; 32 of these were in the vicinity of Jørgen Brønlund Fjord , and 2 were situated directly south of Kap Morris Jesup. The chemistry of the water was analyzed in the majority of the localities, and temperature recordings were made throughout the summer. In connection with these studies, samplings of freshwater Entomostraca were taken at regular intervals; 6 of the localities proved to be devoid of Entomostraca, in 4 cases as a result of premature drying up , in one because of excessive salt contents, and in one because of extremely low temperature. A total of 15 species of freshwater Entomostraca was found in the remaining localities; 8 of the species, namely, Bosmina longirostris, Macrothrix hirsuticornis, Candona candida, Candona lapponica, Candona groenlandica, Limnocythere sanctipatrici, Limnocalanus macrurus, and Maraenobiotus brucei, were observed in Peary Land for the first time. On the basis of measurements of most of the specimens obtained an attempt will be made to determine the life cycle of the species under most extreme conditions, and their geographical distribution will also be treated.